Faktor yang mempengaruhi adopsi dengan mediasi peran intention to use mandiri mobile banking di Surabaya - Dimaz Brahmantyo Hari Pratama Putra; Basuki Rachmat (Universitas Hayam Wuruk Perbanas, 2021)
This study was aimed to determine the effect of the perceived usefulness, perceived ease of use, perceived Trust, Social Influence, perceived risk, and Perceived Security on Adoption, with the Mediation Role of Intention to Use Mobile banking by Bank Mandiri Customers in Surabaya. This is a quantitative research with survey approach with the sample of 180 respondents. They were taken from from Bank Mandiri customers in Surabaya who have used Mobile banking services. The data were analyzed and the hypotheses were tested using the structural equation model method with the Smart-PLS program. The result showed that each of Perceived Usefulness, Perceived Ease of Use, Perceived Trust, Social Influence, Perceived risk, and Perceived Security had a significant effect on Intention to Use. Meanwhile, Intention to Use has a significant effect on Adoption. Each independent variables, namely Perceived Usefulness, Perceived Ease of Use, Perceived Trust, Social Influence, Perceived risk, and Perceived Security toward Adoption is mediated by Intention to Use. It can be implied that the important role of Intention to Use Mobile banking which must be continuously encouraged by Bank Mandiri. Intention to Use can push effect of Perceived Usefulness, Perceived Ease of Use, Perceived Trust, Social Influence, Perceived risk, and Perceived Security on Mobile banking Adoption at Bank Mandiri in Surabaya.